CBMT-32. EGFR SUPPRESSES p53 FUNCTION THROUGH DNA-PKcs BINDING TO p53: NOVEL CROSSTALK BETWEEN EGFR AND TP53 IN GLIOBLASTOMA. (11th November 2019) - Ding, Jie; Li, Xiaolong; Zhang, Chen; Gao, Feng; Wu, Shaofang; Wasylishen, Amanda; Baggerly, Keith; Lozano, Guillermina; Koul, Dimpy; Yung, Alfred
Abstract: Comprehensive analysis of the TCGA Glioblastoma database has identified 3 prognostically relevant subgroups (Proneural, Classical and Mesenchymal). Interestingly, it has also revealed a near mutual exclusivity of EGFR amplification and TP53 mutations. There are only a few tumors with both amplified EGFR and mutant TP53 . We decided to investigate the functional relationship between EGFR and TP53 relative to tumorigenesis and tumor proliferation. We selected from our molecularly characterized GSC bank a series of EGFR amplified+ TP53wt / TP53mut lines for this study. Here we report that EGFR amplification overrides the effect of p53wt but co-regulates tumorigenesis with TP53R175H mutation. We show that CRISPR EGFR knockout in TP53wt cells leads to complete loss of cell growth suggesting that EGFR is essential for cell survival, providing growth signal and suppression of p53wt function. We further show that EGFR induces physical binding between p53wt and DNA-PKcs, which suppresses p53wt by inhibiting p53 phosphorylation at S15. The knockdown of DNA-PKcs restores p53wt anti-tumor function. In contrast, GSC262 harboring TP53R175H mutation is the only GSC that survives after EGFR knockout, suggesting that this specific mutation has a gain of function (GOF) to sustain growth without EGFR . This is confirmed by dual knockout of EGFR and TP53R175H showing no surviving cells. Further investigation shows both EGFR and p53R175H induce tumor glycolysis, the major energy metabolism and heightened growth signal for this group. We further show that EGFR mediated suppression of p53R175H is through DNA-PKcs binding to p53R175H and reduced S15 phosphorylation. Taken together, this study reveals 1) EGFR amplification is essential for tumor growth in TP53wt GSCs; 2) novel crosstalk between EGFR and p53 through DNA-PKcs. 3) EGFR suppresses p53wt function by providing the energy required for tumor growth through inducing glycolysis, and 4) TP53R175H is a GOF mutation that sustains life without EGFR by inducing glycolysis.